On Araniella and Neoscona (Araneae, Araneidae) of the Caucasus, Middle East and Central Asia - Zamani, Alireza (Zookeys, 2020)
Abstract. New taxonomic data for species belonging to Araniella Chamberlin & Ivie, 1942 and Neoscona Simon, 1864 occurring in the Caucasus, Middle East and Central Asia are provided. Three species are described as new to science: A. mithrasp. nov. (♂♀, northwestern, central and southwestern Iran), A. villaniisp. nov. (♂♀, southwestern Iran, eastern Kazakhstan and northern India) and N. isatissp. nov. (♂♀, central Iran). Neoscona spasskyi (Brignoli, 1983) comb. nov., stat. res. is removed from the synonymy of N. tedgenica (Bakhvalov, 1978), redescribed and recorded from Iran and Turkmenistan for the first time. New combinations are established for this species, as well as for Araniella nigromaculata (Schenkel, 1963) comb. nov. (♀, north-central China) (both ex. Araneus). Two new synonymies are proposed: Araniella tbilisiensis Mcheidze, 1997 syn. nov. is synonymized with A. opisthographa (Kulczyński, 1905), and Neoscona sodom Levy, 1998 syn. nov. is synonymized with N. theisi (Walckenaer, 1841); the latter is recorded from Iran, Georgia, and Russia (Northern Caucasus) for the first time.